An evaluation of the impact of Kruger National Park's development programme on the Hlanganani community in Limpopo - Shikolokolo, Hasani Patrick (My University, 2010)
The Kruger National Park is a world renowned organization and is rated as one of the best nature reserves in nature conservation in the world. Despite all the efforts made to control and protect nature in the Park, there is a need for the involvement of the community around the Park. Community-based conservation in particular has been subjected to a series of scathing criticisms, and it has become increasingly acceptable to advocate a return to more coercive forms of conservation. The establishment of the Park forum consisting of the neighbouring communities and the Park requires new strategies for better integration of conservation and rural development. The interest of conservation can be threatened by various factors, mainly poverty, poaching and wildlife conflicts. The interests of the population residing in the immediate neighbourhood of Kruger National Park can be threatened by proposed wildlife management options, other neighbouring conservation areas, and new tourist development activities. Effective conflict prevention mechanisms need to be developed together with the communities and especially in the implementation process. The study presents a critical analysis of the impact of the development made by the Park to the local communities. The available policies need to be implemented in order to assess their developmental impact they are making on the communities. The community has developed a negative attitude towards the park because they think the park is not doing enough in terms of development and training and skills development. The issue of a budget is a concern because it is not clear whether the park has a budget or not for the community. In as far as the community is concerned, there is no budget available and in as far as the park is concerned, the budget is available for community development. There is no cooperation between the park and the community. It seems the park is operating parallel to the community. There are a lot of uncertainties on the side of the community which has developed into mistrust. Communities like Makuleke are involved in farming such that some of the community members have got some subsistence farming skills. If training may be given to these people, most of them may begin to engage in commercial farming. There is also a strong feeling that the Hlanganani forum which represents the community is not recognized by the KNP management. It is there to fulfill the requirement of the policy. It became clearly that Kruger National Park does not involve the forum which has been formed to function as a link between the Park and the community. The negotiated partnership between the park and the community in terms of nature conservation is now at stake. The community is now more concerned about their safety and that of their livestock because of the wild animals roaming around day and night. This is a very serious problem which exists between the park and the community which in a way may hamper the progress in terms of sustaining the relationship 5 currently being nurtured. It is recommended that the park management as the main active role player should put in place a good, viable and effective communication strategy which will form the basis of communication between the park and the community. This will assist both the park and the community to communicate the available developmental policies to the community. And if that is well communicated it is going to eliminate unnecessary conflict in terms of not knowing what the park has for the community and the policies available to address such developmental issues.
M Sc (Botany) --University of Limpopo, 2010
Keywords: National Parks - South Africa; Rural development; Community-based conservation; Poaching; 333.70968; National Parks - South Africa; Rural Development